DAMPAK PENERBITAN SK.903/MENLHK/SETJEN/PLA.2/12/2016 TENTANG KAWASAN HUTAN PROVINSI RIAU TERHADAP KEPEMILIKAN TANAH PADA MASYARAKAT DI KECAMATAN LUBUK BATU JAYA KABUPATEN INDRAGIRI HULU - Annisa Fitria Habibah; Maryati Bachtiar; Setia Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Ownership rights to land are regulated in Article 20 of the Basic Agrarian Law, whichstipulates that land ownership is an hereditary, strongest, and fullest right that individuals canhave over land, with a social function. The issuance of Minister of Environment and ForestryDecree Number 903/MENLHLK/SETJEN/PLA.2/12/2016 regarding the Forest Area in Riau Province changes the status of theregion to a forest area. One of the areas affected by this change is the Lubuk Batu Jaya Sub-district in the Indragiri Hulu Regency, where the residents have settled prior to the reform in1997 and received goverment assistance, such as land for residence and cultivation, especiallyfor transmigrants. As of now, there is still no clarity regarding the status of land ownership forthe community whose land falls within the forest area based on the ministerial decree. Theobjective of this research is to understand and analyze the impacts resulting from the issuance ofMinister of Environment and Forestry Decree Number 903/MENLHK/ SETJEN/PLA.2/12/2016on land ownership in the Lubuk Batu Jaya Sub-District. Additionally, the research aims toidentify efforts to resolve land ownership issues for the community after the implementation ofthe aforementioned decree.The research methodology employed in this study is sociological. The study is conductedin The Lubuk Batu Sub-district, Indragiri Hulu Regency, Riau. The population and samplesinclude Section 2 of the land office in the Indragiri Hulu Regency, the sub-district head of LubukBatu Jaya, the community of Lubuk Batu Jaya Sub-district (Pondok Gelugur Village, RimpianVillage, and Lubuk Batu Tinggal Village), and the founders of the Non-GovermantalOrganization Forest Rescue Network Riau (JIKALAHARI). The Data sources include primary,secondary, and tertiary data, with data collection techniques involving interviews and literaturereviews.The impacts related to land ownership for the residents of Lubuk Batu Jaya Sub-districtwithin the Riau Province Forest Area after the issuance of Minister of Environment and ForestryDecree Number 903 include the inability of of residents to obtain funds for Smallholder Oil PalmRejuvenation (PSR), inability to apply for loans with Land Certificate (SHM) collateral, andinability to engage in land transcaction. This is due to the lack of clarity regarding the legalityof land ownership certificates held by the community, preventing them from performing legalaction that require SHM legality.Keywords: Land Ownership, Forest Area, Legal Certainty